Control of Polymer Properties by Entanglement: A Review - Kong, De‐Chao; Yang, Ming‐Hao; Zhang, Xue‐Song; Du, Zu‐Chen; Fu, Qiang; Gao, Xue‐Qin; Gong, Jia‐Wei (Macromolecular materials and engineering, 2021)
Chain entanglement, either cohesional or topological, distinguishes polymers from other engineering materials. It impedes the movement of molecular segments and influences the polymer rheology, morphology, and mechanical properties. Although a high level of entanglement can increase the polymer toughness, excessive entanglement should be avoided because it causes a high melt viscosity making the processing difficult. This review tended to elucidate the influence of entanglement on the polymer structure, determining the material properties and processability. A wide range of methods used to fine control the degrees of chain entanglement are summarized. The methods are applicable to polymers in solutions, melts, and condensed states with advantages and limitations discussed in detail. The authors also examined the effect of the entanglement on polymer crystallization—the mechanism remains a controversial issue. This review will provide general guidance to designing and processing polymer materials with desired properties via a rational route of controlling the chain entanglement. In this work, a wide range of methods used to fine control the degrees of chain entanglement are summarized. The methods are applicable to polymers in solutions, melts, and condensed states with advantages and limitations discussed in details. This review will provide general guidance to designing and processing polymer materials with desired properties via a rational route of controlling the chain entanglement.